2010
DOI: 10.1007/s00423-010-0631-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based use of enteral nutrition in acute pancreatitis

Abstract: Although enteral nutrition is undoubtedly a key component of the management of acute pancreatitis, the exact role of that is needed to be defined yet. In particular, conflicting data from studies on nutrient compositions will require further clarification in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
1
22
0
1
Order By: Relevance
“…59 The major benefits from early feeding appear to be effective only if feeding is commenced within the first 48 hours following admission, 60 and the current recommendation based on a 2010 meta-analysis of 32 RCTs is to commence oral feeding at the time of admission if tolerated or within the first 24 hours. 60,61 Finally, a low-fat diet was shown to be preferable to clear fluids on admission for mild acute pancreatitis owing to a higher caloric intake with no associated adverse effects. 57,58 There is no evidence to suggest that a low-fat diet is preferable to a regular diet.…”
Section: Nutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…59 The major benefits from early feeding appear to be effective only if feeding is commenced within the first 48 hours following admission, 60 and the current recommendation based on a 2010 meta-analysis of 32 RCTs is to commence oral feeding at the time of admission if tolerated or within the first 24 hours. 60,61 Finally, a low-fat diet was shown to be preferable to clear fluids on admission for mild acute pancreatitis owing to a higher caloric intake with no associated adverse effects. 57,58 There is no evidence to suggest that a low-fat diet is preferable to a regular diet.…”
Section: Nutritionmentioning
confidence: 99%
“…Several meta-analyses have shown similar results, with significant reductions in infectious complications, mortality and multiorgan dysfunction when enteral nutrition is commenced within the first 48 hours following admission. 61,63,64 A meta-analysis 65 of 4 prospective studies of patients with predicted severe acute pancreatitis (n = 92) demonstrated no change in intolerance of feeding (RR 1.09, 95% CI 0.46-2.59, p = 0.84) or in mortality (RR 0.77, 95% CI 0.37-1.62, p = 0.5) when given enteral feeds by nasogastric feeding tube versus nasojejunal feeding tube. In a more recent metaanalysis of 3 RCTs (n = 157), Chang While no high-quality RCTs exist on this topic, to date there has been no evidence to suggest that enteral feeds should be delayed for the purposes of acquiring a nasojejunal feeding tube, especially in light of morbidity and mortality benefits of commencing enteral feeds within the first 48 hours.…”
Section: Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em quase todos os desfechos estudados nessa metanálise, a NE foi superior à NP, com razão de chances de 0,5 para mortalidade (intervalo de confiança de 95% -IC 95% 0,26-0,97), 0,33 para infecções (IC 95% 0,2-0,54) e 0,32 para disfunção orgânica (IC 95% 0,18-0,56). O risco muito reduzido de infecções encontrado em pacientes com NE pode justificar a redução da mortalidade do mesmo grupo, tendo em vista a gravidade da infecção e sepse como complicadores dos casos de PA. Oláh et al 80 atualizaram a metanálise em 2010 incluindo mais oito ensaios clínicos, encontrando amplo benefício na redução da mortalidade em pacientes em vigência de NE na grande maioria dos estudos. Disfunção orgânica também foi estudada por Wu et al 81 , que encontraram em estudo de coorte retrospectivo de 107 pacientes adultos incidência quatro vezes maior de disfunção orgânica em pacientes que receberam NP prolongada quando comparados aos que receberam NE.…”
Section: Aspectos Nutricionaisunclassified
“…5,7,12,13 EN remains an integral part of management, which has been associated with a lower incidence of infection, multiorgan failure, lower mortality rates, and a shorter hospital stay in adult patients with AP according to recent meta-analyses. [14][15][16] In a state of AP, there is increased gut permeability that promotes the development of systemic inflammation and could allow bacterial translocation, which could lead to more severe disease course.…”
Section: Discussionmentioning
confidence: 98%